Effects of Planting Time of Sugarcane on Borers Damage and Control Benefits - Huiwen HUANG; Dewei LI; Tao LI; Juju LIANG; Zhenqiang QIN; Yawei LUO (Guangdong nongye kexue)
【Objective】The borers damage and chemical control effectiveness of sugarcane planted at different time were analyzed in this study, providing a base for choosing the suitable planting time of sugarcane and for the scientific utilization of pesticide against stem borers, in order to supply technical support for ensuring high and stable yield in sugarcane industry.【Method】In 2018/2019 crushing season, new sugarcane was planted in late December of 2017, in late January, late February, late March and late April of 2018, respectively. The growth of sugarcane and damage caused by borers were investigated. The benefits from controlling and non-controlling borers were compared. Investigations in this study on new-planting sugarcane were conducted for two consecutive crushing seasons to compare the data obtained under different climatic conditions. The planting and survey methods of new-planting sugarcane in 2019/2020 crushing season were consistent with that in 2018/2019 crushing season.【Result】The results show that the dead heart rates caused by the first and second generations of borers in new planting sugarcane tend to decrease with the delayed planting times in the condition without using insecticide. The average dead heart rate caused by the second generation of borers in sugarcane planted in December was as high as 24.90%, while the average dead heart rate in those sugarcane planted in April was low at 8.37%. Different planting times had little affect on the damaged plant rates and damaged internode rates caused by borers at harvest. The dead heart rates of sugarcane seedlings planted in March and April caused by borers were relatively low. The plant height, yield, and sugar content per hectare of sugarcane planted early (in the late December, late January and late February) were higher than those planted later (in the late March and late April), and the early planted sugarcane also showed better economic benefits significantly. Under non-chemical conditions, the average yield and sugar content per hectare of sugarcane planted in December were 102.19 t/hm2 and 15.57 t/ hm2, respectively, while those planted in April were only 47.57 t/hm2 and 6.40 t/hm2, respectively. The total income of cane yield and sugar yield obtained from sugarcane planted in December, January and February increased more than 220% compared to those planted in April. The application of pesticides for controlling borers contributed to the increase in sugarcane yield and sugar content, with a benefit ratio of 1:1.37-1.99 for sugarcane farmers and a total benefit ratio of 1:4.33-5.76 for sugarcane industry. It indicates that control of borers has great importance to the high-quality development of sugar industry.【Conclusion】To improve the supply capacity of raw sugarcane in China, it is suggested that sugarcane be planted from the late December to the late February of the following year in cane regions of Guangxi Province. Combining with borers control, the yield of sugarcane and sugar content can be further increased.